2007
DOI: 10.1103/physrevlett.99.238104
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Breathers in Nonlinear Network Models of Proteins

Abstract: We introduce a topology-based nonlinear network model of protein dynamics with the aim of investigating the interplay of spatial disorder and nonlinearity. We show that spontaneous localization of energy occurs generically and is a site-dependent process. Localized modes of nonlinear origin form spontaneously in the stiffest parts of the structure and display site-dependent activation energies. Our results provide a straightforward way for understanding the recently discovered link between protein local stiffn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
153
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(163 citation statements)
references
References 36 publications
10
153
0
Order By: Relevance
“…Specifically, in the nonlinear network model (NNM) [33,39], the potential energy of a protein, E p , has the following form:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, in the nonlinear network model (NNM) [33,39], the potential energy of a protein, E p , has the following form:…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, their ability to pump energy from neighboring sites is a distinctive signature of DB self-excitation [32], e.g. observed as a consequence of surface cooling [33][34][35][36] or due to modulational instability of band-edge waves in nonlinear lattices [37,38]. Furthermore, within the frame of a nonlinear network model, we have shown that highly energetic DBs can form easily in proteins [33], and that they feature strongly site-modulated properties [39].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, when the thermalized nonlinear systems are cooling by boundary dissipations, long-lived discrete breathers can sometimes be observed after a long time relaxation 48,49,[51][52][53][54][55][56][57][58][59][60][61] .…”
Section: Introductionmentioning
confidence: 99%